Umur Pesalah Kanak-kanak: Ketidakseragaman dalam Enakmen Jenayah Syariah dan Enakmen Tatacara Jenayah Syariah di Malaysia (Kanun: Jurnal Undang-undang Malaysia, 2012)
This article elucidates the provisions from two legislations, Syariah Criminal Enactment and Syariah Criminal Procedure Enactment and compares them with the provisions from Syariah law in relation to the determination of the age and the status of child offenders by virtue of opinions from muslim or fiqh scholars. Such an approach is employed to determine whether both provision are in compliance with the Syariah. The findings however reveals that there is a lacunae in the Islamic legislation pertaining to this issue. Therefore there is a need to reassess and reexamine the existing provisions of law. The analysis shows that the requirement of "baligh" (puberty) in the Syariah Criminal Law Enactments is streghtened by the khilaf of muslim scholars relating to the issue.The determination of the age of young offender in the Syariah Criminal Procedure Enactments in Malaysia as a person who must be above the age of ten but below the age of sixteen, can still be disputed if reference is made to the age of "baligh".Keywords: child offender, young offender, puberty, syariah crimes, Syariah Criminal Procedure.